Production of liquid hydrocarbons from pretreated bio-oil via catalytic deoxygenation with syngas. (August 2015) - Tanneru, Sathish K.; Steele, Philip H.
Abstract: Biomass-derived fast pyrolysis oil (bio-oil) is a potential alternative replacement for conventional transportation fuels. But negative properties such as lower energy density, higher water content and acidity prevent the direct use of pyrolysis oil as a fuel. Catalytic deoxygenation of pyrolysis oils to hydrocarbons has been studied widely with application of high heat and hydrogen pressure. However, consumption of a large amount of expensive hydrogen has remained a problem for this technology. Therefore, development of an efficient and reduced hydrogen deoxygenation method would be desirable. In this study, we have applied catalytic deoxygenation of pretreated bio-oil in the presence of pressurized syngas to produce liquid hydrocarbons. The pretreatment is an oxidation step that converts aldehydes to carboxylic acids that are more conducive to catalytic conversion to hydrocarbons than are raw bio-oils. The pretreated bio-oil allowed performance of a partial deoxygenation step with a low amount of hydrogen (syngas). This partially deoxygenated product was then fully deoxygenated with pure hydrogen to produce hydrocarbons. Properties of the resultant liquid hydrocarbons were analyzed by ASTM standards for transportation fuels. The hydrocarbon mixture obtained by our process was analyzed by Fourier transform infrared spectroscopy, detailed hydrocarbon analysis, nuclear magnetic resonance spectroscopy and simulated distillation. Highlights: Oxidation pretreatment to raw bio-oil followed by deoxygenation was studied. 1st-Stage deoxygenation of bio-oil was successfully performed with syngas. Liquid hydrocarbons produced had an HHV of 45.30 MJ/kg and zero oxygen content. Hydrocarbons mixture was comprised of gasoline (45%), jet fuel (20%) and diesel (30%).